LEGALITAS PEMILIHAN KEPALA DAERAH (Analisis Terhadap PERPPU Nomor 1 Tahun 2014) - Ahmadi Ahmadi (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2017)
This paper raises the theme of Legal Selection of Governors, Regents and Mayors with a focus on reviewing the issuance of PERPPU No. 1 of 2014. The subjects are classified in three (3) substances namely; to reveal the legal construction of the Election of Regional Head Election Act, to investigate the Legality of Procedural Issuance of Perppu No. 1 of 2014, and to analyze the Legal Implications it caused. The results of this study indicate that first, the Constitutional Court's Construction of Law is influenced by the political constellation in parliament. Since 2004-2016, Election Law includes seven rules in the form of Laws, two rules in the form of Perppu, and two in the form of Government Regulation. Second, the issuance of Perppu No. 1 of 2014 on the Election of Regional Head is the President's formal right, administrative parameters on the substantial requirements of the issuance of the Perppu have not been regulated, resulting in weak protection against the exact issuance of the Perppu. The effectiveness of the Perppu is influenced by the President's power network. Third, the Perppu as the President's subjective authority requires the setting of explicit terms for the proper issuance, and not prioritizing the political aspect of the Power's interest